Teachers’ Strategies in Teaching English at Vocational High School in Luwu - Arny Irhani Asmin (Institut Agama Islam Negeri Palopo, 2019)
This paper presents an analysis of teaching strategies of the English teachers at the Vocational High School in Luwu. The qualitative method applied to analyze the strategies implemented by two English teachers of the Computer Network Department in a Vocational High School in Luwu. The data indicated that both teachers followed the 2013 curriculum by applying Scientific Learning Approach which consists of observing, questioning, experimenting, associating, and communicating as the core activity in the learning process. Moreover, both teachers commonly applied cooperative learning method, such as small group discussion and pair work. Unfortunately, the English instructions applied was the same as general English, whereas we knew that teaching English in vocational secondary education should be taken into account as English for Specific Purposes. Other than that, the teachers even use the same textbooks as general high school where the contents are frequently inadequate to the vocational students’ needs. Teacher argued that they have limited time and lack of understanding on how to design the specific teaching materials for students.